2015
DOI: 10.1007/s12024-015-9664-x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal foreign-body granulomatous pulmonary embolization due to microcrystalline cellulose in a patient receiving total parenteral nutrition: all crystals are not what they seem

Abstract: Pulmonary foreign-body granulomatous embolization has been described secondary to crystal precipitation in total parenteral nutrition (TPN) as well as when pharmaceutical tablets are crushed and injected intravenously. Extensive granulomatous embolization may cause pulmonary hypertension and death due to acute cor pulmonale. We report the case of a 34-year old woman who had been receiving TPN post-operatively secondary to complications of a paraesophageal hernia repair. During and following receiving TPN, she … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The slow, more typical development of PH in intravenous drug abusers may be challenging to recognize. However, as seen here and in previous reports, 35 the echocardiographic demonstration of RV dysfunction coupled with the CT demonstration of micronodularity, and mosaic attenuation, in a patient at risk for intravenous injection should raise a clinician’s suspicion of this process. While there is no clear treatment, cessation of exposure should be encouraged in an attempt to avoid progression to life-threatening disease.…”
Section: Discussionsupporting
confidence: 74%
“…The slow, more typical development of PH in intravenous drug abusers may be challenging to recognize. However, as seen here and in previous reports, 35 the echocardiographic demonstration of RV dysfunction coupled with the CT demonstration of micronodularity, and mosaic attenuation, in a patient at risk for intravenous injection should raise a clinician’s suspicion of this process. While there is no clear treatment, cessation of exposure should be encouraged in an attempt to avoid progression to life-threatening disease.…”
Section: Discussionsupporting
confidence: 74%
“…Early and more recent reports of pulmonary intravascular MCC are restricted to case reports and small series which typically describe patients with a history of intravenous drug abuse . Other studies have reported MCC secondary to parenteral injection of oral pain medication in patients receiving total parenteral nutrition (TPN) . Embolization of MCC to lung allografts may damage pulmonary arterial vasculature, eliciting impressive fibroinflammatory reactions.…”
Section: Introductionmentioning
confidence: 81%
“…Pulmonary intravascular MCC and crospovidone can show variable patterns of inflammation such as granulomatous vasculitis or little/no inflammatory infiltrate if the material was recently embolized (acute setting; Figure A) . Damage to small muscular arteries and arterioles leads to obliteration of the vessel lumina, which may result in pulmonary hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] Pulmonary crystal-storing histiocytosis, often seen in conjunction with the underlying myeloma or low -grade B-cell lymphoma, to date, has only been reported in a fine -needle aspiration sample. [ 39 ] Exogenous crystals that may be encountered in lung samples include material from aspiration (e.g., talc, barium),[ 40 ] embolization (e.g., total parenteral nutrition),[ 41 ] and drugs (e.g., clofazimine). [ 42 ] Anthracosis and pneumoconiosis-associated crystals (e.g., silicosis) are best identified in tissue specimens.…”
Section: Discussionmentioning
confidence: 99%